Long term performance of existing portland cement concrete pavement sections – case study (2014)
This paper presents the performance of seventeen rigid pavements made of Portland Cement Concrete (PCC) located in the State of Ohio, USA. The Falling Weight Deflectometer (FWD) testing method was used in a total of 58 km of PCC pavement sections to assess the pavement structural condition. Each section is classified as excellent, good, fair, or poor based on the normalized deflections obtained from FWD tests, spreadability, load transfer, and joint support ratio parameters. The overall performance of the analyzed sections is from good to excellent. The field testing methodology along with the performance data analyses presented in this publication are a valuable tool to evaluate the actual structural condition of pavements and as a result short or medium term rehabilitation programs can be issued to ensure the serviceability of the pavement.